Fiqh Study on the Standard of Kifāyah in a Husband’s Maintenance For Online Content Creators with Fluctuating Income - Rosyidah Rosyidah; Sabilul Muhtadin (Fakultas Agama Islam, 2026)
The expansion of the digital economy has given rise to content creators as a new form of employment characterized by fluctuating and unpredictable income patterns. This development presents challenges for the application of a husband’s maintenance obligation (nafaqah) in Islamic jurisprudence, particularly regarding the determination of kifāyah standards, which were traditionally formulated within relatively stable economic contexts. This study aims to examine the concept of maintenance and kifāyah in classical Islamic legal literature and to reconstruct its application within the context of digital content creation. Employing a qualitative normative-conceptual approach, the study relies on a systematic review of classical fiqh sources, contemporary fatwas, and scholarly works on the digital economy. Data were analyzed through the frameworks of maqāṣid al-sharī‘ah, qawā‘id fiqhiyyah, and Islamic legal reasoning (istinbāṭ). The findings indicate that kifāyah is inherently flexible and contextual, emphasizing the fulfillment of essential family needs according to prevailing customs (‘urf) and the husband’s actual financial capacity. In the context of fluctuating digital income, kifāyah is assessed through three interconnected parameters: the lawfulness of income sources, sustainable material adequacy, and income stability supported by prudent financial management and risk mitigation. The study concludes that content creation can constitute a legitimate source of family maintenance when these criteria are fulfilled, thereby offering a contextual framework for contemporary Islamic family jurisprudence in the digital era.